Trigone ventricular meningiomas: Surgical approaches - Zanini, Marco Antonio [UNESP]; Faleiros, Antonio Tadeu Souza [UNESP]; Almeida, Carlos Roberto; Clara, Carlos Afonso; Gabarra, Roberto C. [UNESP] (FapUNIFESP (SciELO), 2011)
Objective: Report our experience with trigone ventricular meningiomas and review the surgical approaches to the trigone. Method: From 1989 to 2006, six patients with meningiomas of the trigone of the lateral ventricles underwent microsurgical resection. Their clinical features, image, follow up, and surgical approaches were retrospectively analyzed. Results: Five patients presented with large and one with small volume meningioma. Unspecific symptoms occurred in three patients; intracranial hypertension detected in three patients; homonymous hemianopsy in three; and motor deficit present in one patient. Three patients were operated by transparietal transcortical approach, two by middle temporal gyrus approach, and one by parieto-occipital interhemispheric precuneus approach. Total resection was achieved in all patients without additional deficits. Conclusion: Judicious preoperative plan, adequate knowledge of anatomy, and use of correct microsurgical techniques are fundamental in achieving complete resection of trigone meningioma with low morbidity.
Meningiomas do trígono ventricular: Abordagens cirúrgicas
Keywords: Lateral ventricle; Meningioma; Surgical approach; Trigone